Akomodasi Nilai-Nilai Pluralisme dalam Acara Adat Rambu Solo di Toraja (Analisis Urf) - Patiara, Syahril Bin; Marwing, Anita; Arif, Firman Muhammad (Palita: Journal of Social Religion Research, 2024)
This research discusses the rambu solo' tradition in Toraja, the value of pluralism in the tradition, and urf analysis related to the rambu solo' procession. This research uses a qualitative method with a legal sociological approach, empirical, and urf analysis. The rambu solo' ceremony is divided into several levels: 1) disili', for lower castes and infants; 2) di pasangbongi, for free people with a short procession; 3) dibatang/didoya tedong, for the middle and upper classes; and 4) rapasan, specifically for nobles. This tradition reflects the value of pluralism through togetherness in the 3S (Sikamali, Siangga', Siangkaran). Urf in rambu solo' includes shahih urf, except for some additional customs that do not conflict with Islamic law. Keywords: Pluralism Values, Rambu Solo Toraja, Urf Analysis